The prevalence of HIV among MSM in China: a large-scale systematic analysis - Dong, Meng-Jie; Peng, Bin; Liu, Zhen-Feng; Ye, Qian-ni; Liu, Hao; Lu, Xi-Li; Zhang, Bo; Chen, Jia-Jia (BMC infectious diseases, 2019)
The prevalence of HIV among men who have sex with men (MSM) has become a significant public health challenge. The aim was to comprehensively estimate the national prevalence of HIV among MSM and its time trends through a large-scale systematic analysis. Systematic search of Cochrane Library, PubMed, EMBASE, CNKI, VIP, and Wanfang Data databases without language restriction for studies on the prevalence of HIV among MSM published before Dec.31, 2018. Studies were eligible for inclusion if they were published in the peer-reviewed literature and used validated assessment methods to assess the prevalence of HIV among MSM. Estimates were pooled using random-effects analysis. Data were extracted from 355 cross-sectional studies (571,328 individuals) covered 59 cities from 30 provinces and municipalities of China. The overall national prevalence of HIV among MSM from 2001 to 2018 was estimated to be 5.7% (95% CI: 5.4-6.1%), with high between-study heterogeneity (I = 98.0%, P <  0.001). Our study showed an increased tendency in the HIV prevalence as time progressed by meta-regression analysis (I = 95.9%, P <  0.0001). HIV prevalence was the highest in those aged 50 years and older with HIV prevalence of 19.3% (95%CI: 13.1-27.4%, N = 13). HIV was more prevalent in the illiterate population (16.8%), than in those who had received an education. Although the internet was a major venue for Chinese MSM seeking male sex partners (35.6, 95%CI: 32.3-39.9%, N = 101), seeking MSM in bathhouses/saunas had the highest associated prevalence of HIV (13.4, 95%CI: 10.3-17.1%, N = 22). The HIV prevalence among MSM varied by location: compared with other regions in China, HIV was highly prevalent among MSM in the southwest (10.7, 95%CI: 9.3-12.2%, N = 91). Compared to participants who sometimes or always used condoms, participants who had never used a condom in the past 6 months had a higher risk of HIV infection, with odds ratios of 0.1 (95%CI: 0.08-0.14). Our analysis provided reliable estimates of China's HIV burden among MSM, which appears to present an increasing national public health challenge. Effective government responses are needed to address this challenge and include the implementation of HIV prevention.